IPTEK Bagi Masyarakat (IbM) Melalui Peningkatan Panen Pedet dan Produksi Kompos Berkualitas Pada Kelompok Ternak Sapi Potong - Bayu Andri Atmoko; Endang Baliarti; Nanung Agus Fitriyanto (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2019)
Beef Cattle have a role as saving for farmers to continue their business, although not profitable based on business analysis. Therefore, the right strategy is needed according to the problems of both the culture and the resources of farmers. The community service activity was conducted in a beef cattle farmer groups as cattle breeding for calf production, namely, are Mergo Andini Makmur and Sumber Ayu in Sleman Regency. The beef cattle productivity in the two groups is not good, S/C is more than twice, even up to four times, postpartum estrus is more than one year, and calving interval is more than 2 years. The beef cattle farmer groups have already diversified their business, which is the processing of manure and waste product of cattle, but not yet optimal. Community service is carried out to improve reproductive performance of cattle through the providing of a superior bull for bull stimulation, counseling, assistance in the prevention of worm infections, and demonstrations of compost and feed quality production. The first stage is preparation, including consolidation with the member farmer groups, followed by the socialization of the activity program. The next stage of implementation, by conducting reproductive and breeding management counseling, cattle health management, feed processing and management, and compost production. The result of the implementation of a bull stimulation for one month is based on the emergence of estrus (more than 50%) following by a conception rate (33.33%) of the cows population, and the level of participatory farmers. The demonstration of the fermented straw feed and compost is also implemented as a supporting activity.